Goodness of Cloud Computing: does Bangladesh ready for it - Hasan , Md. Ahsan ul (Global Disclosure of Economics and Business, 2013)
Technology is playing a vital role in all aspect of our lives. Last decade has seen information and communication technologies dramatically transforming the world, enabling innovation and productivity increases, connecting people and communities, and improving standards of living and opportunities across the world. Even though global economy has been turbulent during last several years, governments and organizations trying to keep the momentum going and last couple of years “Cloud Computing” becoming fast-growing technology phenomenon. Cloud Computing can provide fundamental contribution to efficiency in public and private sectors as well as it can also promote growth, competition and business creation. The purpose of this study is to portrait whether developing countries like Bangladesh can be benefited from cloud computing, and also finds out Bangladesh’s readiness to take full advantage of it.JEL Classification Code: L86; C89